2002
DOI: 10.1080/088800102753541297
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Granulosa Cell Tumors in Childhood

Abstract: Granulosa cell tumors (GCT) of the ovary are prepubertal in 5% of the patients. In girls less than 20 years old, 80% of GCTs differ from those among adults. These juvenile granulosa cell tumors (JGCTs) are usually benign. GCTs belong to ovarian sex cord-stromal tumors, the more common ovarian tumors being epidermal and germinal. The etiology of GCT remains unknown. Most young children with GCT present with precorious pseudopuberty. Among adolescents GCT often causes menstrual irregularities, virilization, abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 41 publications
0
61
0
Order By: Relevance
“…GCTs are also highly vascularized and hemorrhagic and may present as large abdominal masses with acute abdominal pain (1). The median age of diagnosis in the adult subtype of GCT is 50-54 years, while the more uncommon juvenile subtype (5%) is diagnosed in children and adolescents (3,4). Generally, GCTs are diagnosed at an early stage and are considered to have relatively good prognosis with more than 90% 5-year survival rate (1).…”
Section: Introductionmentioning
confidence: 99%
“…GCTs are also highly vascularized and hemorrhagic and may present as large abdominal masses with acute abdominal pain (1). The median age of diagnosis in the adult subtype of GCT is 50-54 years, while the more uncommon juvenile subtype (5%) is diagnosed in children and adolescents (3,4). Generally, GCTs are diagnosed at an early stage and are considered to have relatively good prognosis with more than 90% 5-year survival rate (1).…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperandrogenism in granulosa cell tumors of the ovary has been reported by several investigators [1,7,8,18,19,20,21,22], its pathophysiology has not been elucidated so far. We recently showed that low or absent expression of SOX9 along with aberrant expression of FOXL2 in granulosa cell tumors of the testis could be associated with a transdifferentiation of tumoral cells from male to female type [9].…”
Section: Discussionmentioning
confidence: 99%
“…Other less frequent tumors in this class are thecoma fibromas, Sertoli cell tumors, sex cord tumors with annular tubules, and gynandroblastomas [1]. Ovarian granulosa cell tumors are further divided into two subgroups: juvenile and adult tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Ascites in 10% of them is reported [4]. This tumor can present in divers ages from infancy to teenage but it mostly presents in the age of 8 or 9 years old [5].…”
Section: Introductionmentioning
confidence: 99%